2015
DOI: 10.1088/2041-8205/801/2/l21
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Masses and the Non-Radial Drag Coefficient of a Solar Coronal Mass Ejection

Abstract: Decades of observations show that CMEs can deflect from a purely radial trajectory yet no consensus exists as to the cause of these deflections. Many of theories attribute the CME deflection to magnetic forces. We developed ForeCAT (Kay et al. 2013(Kay et al. , 2015, a model for CME deflections based solely on magnetic forces, neglecting any reconnection effects. Here we compare ForeCAT predictions to the observed deflection of the 2008 December 12 CME and find that ForeCAT can accurately reproduce the observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(38 reference statements)
4
14
0
Order By: Relevance
“…This paper and previous work (Capannolo et al, ; Kay, dos Santos et al, ; Kay et al, ; Kay, Gopalswamy, Xie, et al, ) have shown that ForeCAT can reproduce the deflection and rotation of observed CMEs, given the correct input parameters. Future work will allow ForeCAT to be useful for actual predictions.…”
Section: Discussionsupporting
confidence: 62%
“…This paper and previous work (Capannolo et al, ; Kay, dos Santos et al, ; Kay et al, ; Kay, Gopalswamy, Xie, et al, ) have shown that ForeCAT can reproduce the deflection and rotation of observed CMEs, given the correct input parameters. Future work will allow ForeCAT to be useful for actual predictions.…”
Section: Discussionsupporting
confidence: 62%
“…The peculiarity of this CME definitely lives in the reversal in latitudinal deflection, very different than previous CME successfully matched by ForeCAT (Kay et al 2015a(Kay et al , 2016(Kay et al , 2017. We show in this work how ForeCAT can still reproduce the complex CME trajectory after taking into account magnetic tension and magnetic forces only, if we include an appropriate initial nonradial velocity and a linear angular width expansion law.…”
Section: Summary and Discussionmentioning
confidence: 68%
“…ForeCAT has successfully matched several observed CME trajectories (Kay et al 2015a(Kay et al , 2016(Kay et al , 2017. Here, we explore a more complex CME, ejected on 2008 April 9 (during solar minimum of cycle 24) at 9:25 UT.…”
Section: Introductionmentioning
confidence: 87%
“…For all free parameters, the behavior at distances below the coronagraph field-of-view is largely unconstrained. To determine tighter constraint on these unknown paramters, as done in Kay et al (2015a) and Pisharody et al (2016), we determine a best fit to the observations by sampling parameter space for the unknown ForeCAT input parameters. We determine the reduced chi-squared, χ 2 ν ,…”
Section: Variation With Forecat Parametersmentioning
confidence: 99%